The Relationship of Risk Factors for Medication Error in the Electronic Prescription Prescribing Phase in the Outpatient Pharmacy Installationof Hospital X - Sekar Pratiwi, Arum; Endah Lestari, Yovita; Annisa Primadiamanti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Backrgound: Medication errors are avoidable drug misuse incidents that occur during the drug administration process. Medication errors occur at various stages, such as writing a prescription (prescribing), translating a prescription (transcribing), providing and compounding medication (dispensing) and administering medication (administration. Prescribing errors are the most common type of error found in prescription services. Objective: This study was conducted to determine the percentage of medication errors in the prescribing phase of electronic prescriptions and the relationship between prescription characteristics, including the clinic where the prescription was issued, the type of drug, and the number of drugs, with the occurrence of medication errors. Methods: The study was conducted as a retrospective, non-experimental, observational cross-sectional study. The study used electronic prescription data from outpatient pharmacy installations from January to February 2025, with a total of 400 samples. A description of medication error events and an analysis of the relationship between variables were performed using the Chi-Square test. Results: The results showed that medication errors in administrative requirements were 100%, pharmaceutical requirements were 69.5%, and clinical requirements were 80%. There was a significant association between polyclinic origin of prescription and medication error in pharmaceutical and clinical requirements (p-value < 0.05). There was a significant relationship between drug type and medication error in pharmaceutical and clinical requirements (p-value < 0.05). There was a significant relationship between the number of drugs and medication errors in pharmaceutical and clinical requirements (p-value < 0.05). Conclusion: This study reveals a relationship between risk factors, including the polyclinic origin of the prescription, type of drug, and number of drugs, and the occurrence of medication errors in the prescribing phase.